The effect of economic vulnerability on the participation in development programs and the socio-economic well-being of low-income households - Wan Mustapa, Wan Nurulasiah; Al Mamun, Abdullah; Ibrahim, Mohamed Dahlan (2018)
This study intends to examine the effect of economic vulnerability on participation in development initiatives, household income, micro-enterprise income and net worth of microenterprise asset among low-income households in the state of Kelantan, Malaysia. Adopting a cross-sectional design, this study collected data from randomly selected 450 micro-entrepreneurs who were being served by three major development organizations in Kelantan, Malaysia. The findings revealed that the level of economic vulnerability among the respondents had a significantly negative effect on the participation of development initiatives, household income, micro-enterprise income and the net worth of microenterprise asset among the low-income Kelantanese households. This study provided insights for a comprehensive policy formulation for rural development as it identified program participation issues and gaps faced by the targeted cohort, which if effectively addressed can lead to an increase in participation in development programs, together with household and micro-enterprise income and assets, among the low-income economically vulnerable households in Kelantan, Malaysia.